2012
DOI: 10.1108/19348831211215641
|View full text |Cite
|
Sign up to set email alerts
|

The concept of alienation: towards conceptual clarity

Abstract: Purpose -Although alienation as a concept has a rich history, it has suffered relative neglect in organizational studies and one possible reason for the same is its conceptual ambiguity vis-à -vis popular and long-standing concepts of commitment/identification, satisfaction and engagement, that represent the positive experience of work and which have sometimes been equated as the opposite of work alienation. Similarly, the negative experience of work has traditionally been captured by concepts such as burnout/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 102 publications
1
67
1
4
Order By: Relevance
“…Previous literature has already shown that alienation leads to a state of depression [1]. In this study, however, it was shown that work alienation is associated with depressiveness as a personality trait.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…Previous literature has already shown that alienation leads to a state of depression [1]. In this study, however, it was shown that work alienation is associated with depressiveness as a personality trait.…”
Section: Discussioncontrasting
confidence: 67%
“…He viewed work alienation "as a generalized cognitive state (or belief) of psychological separation from work insofar as work is perceived to lack potentiality for satisfying one's salient needs and expectations" [3] (p. 131). A number of other researchers have also suggested that if employees experienced low satisfaction or frustration of relevant psychological needs in a job context, they become alienated [1,4,5]. Similar to previous theories that applied a motivational approach [1,[3][4][5], we assume that work alienation is a complex state in which a person is not interested in their work, does not like it, and considers it to be replaceable.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations